Evaluation of an immersive virtual reality-based position control interface for a SCARA robotic arm - Condori, Victor; Castillo, Jaime; Mamani, Alfredo; Pari, Lizardo (Eastern-European Journal of Enterprise Technologies, 2025)
This research explores the use of SCARA robotic arms operated through Immersive Virtual Reality (IVR) interfaces, enhancing human-robot interaction for remote manipulation tasks. The problem addressed is the limited understanding of how non-expert users perform with such systems in teleoperation, compared to conventional control methods. While IVR offers immersive interaction, its effectiveness for users with limited teleoperation experience remains underexplored. To address this, an IVR-based system was developed to allow natural user interaction for executing pick-and-place tasks. Users control robotic arms in real time within a virtual environment using hand gestures and spatial interaction. Experimental evaluation involved twelve participants performing standardized tasks with both IVR and conventional interfaces. Performance was measured through execution time, success rate, and user experience using NASA-TLX and SUS metrics. The results show that the IVR reduces overall mental workload by approximately 45% and improves perceived usability by 15.9 points out of 100 compared to the traditional interface. Compared to conventional interfaces, participants completed tasks faster, with higher success rates and lower mental and physical demand. These improvements are due to the immersive nature of the IVR environment, which enhances spatial awareness and simplifies control of the robotic system. Real-time visual feedback further contributed to efficient interaction. The findings suggest the IVR interface is especially suitable for tasks requiring high operator involvement, such as remote manipulation in hazardous environments, training simulators, and educational robotics. Future work should optimize the interface for broader user tasks and capabilities